Conflicto armado y feminismo de Estado: la incursión de la problemática de la guerra en la acción pública para las mujeres en Colombia (Tema Central) - Vergel Tovar, Carolina (2018)
Parting from a panoramic point of view on the Colombian state public policies on women issues, this paper aims to describe and analyze the process through which the problems of women victims of armed conflict became part of public policy in the country. The analysis is also focusing on identifying the difficulties that surrounded the emergence of this problem as a problem of public interest, and therefore allows to appreciate and discuss other processes of institutional and legal order. More specifically, the article looks forward to contribute to the study of the construction of a “State feminism”, and also to the discussion concerning the adoption of a gender perspective in human rights policies and transitional justice.